A PRAGMATIC ANALYSIS OF PERSONAL DEIXIS IN ENGLISH TRANSLATION OF AL QUR’AN - UPURNASARI , JLIARI (2007)
This study is aimed at describing the types of personal deixis and finding the reference of personal deixis. The object to be analyzed is personal deixis in the form of words. The writer takes the data from English Translation of Al -Qur’an chapter 29 and 30 based on lists of turned Al -Qur’an chapters . In collecting data, the writer uses documentation method by reading and selecting the personal deictic words, which can be found in those chapters. In clarifying the types of personal deixis the writer uses pragmatics analysis especially deixis theory. In finding out the reference of personal deixis, the writer employes reported speech theory by Hurford and Brendan. This study shows that 1) there are three types of personal deixis they are: first personal deixis, second pesonal deixis, and third personal deixis. 2) there are three references in personal deixis, they are: the reference which refers to first person, the reference which refers to second person, and the reference which